SOSIALISASI PENERAPAN TEKNOLOGI MODIFIKASI CUACA UNTUK PENGENDALIAN BENCANA BANJIR - Tukiyat; Makhsun; Murni Handayani; Hesti Rahayuningsih; Hartanto (Abdi Jurnal Publikasi, 2025)
The increasing intensity of climate change has triggered a rise in the frequency and impact of hydrometeorological disasters in Indonesia, such as floods, droughts, and forest fires. This condition demands the strengthening of community capacity in understanding and anticipating disaster risks. This Community Service (PKM) activity aims to educate the people of Ciomas District, Bogor Regency, about hydrometeorological disaster mitigation and the introduction of Weather Modification Technology (WMT) as an adaptive solution. The implementation methods included seminars, counseling sessions, interactive discussions, and evaluations through pre-tests and post-tests. The results show that the majority of participants came from civil servants and village apparatus (48%), with 83% stating that the material was easy to understand. A significant increase in understanding was recorded from pre-test to post-test, indicating effective material delivery. Additionally, participants expressed high enthusiasm for utilizing technology in disaster management, particularly WMT. These findings reinforce the importance of continuous dissemination of disaster information through information technology to the public. This activity contributes positively to building community preparedness in facing climate change and supports collaboration between academia, government, and the public in scientific-based disaster mitigation strategies. In the future, further assistance is needed to encourage the local implementation of adaptive technologies.